PELAKSANAAN PELAYANAN PUBLIK OLEH DINAS PERHUBUNGAN KOTA PEKANBARU (Studi Kasus Pengelolaan Parkir Di Kecamatan Sukajadi) - HELMI OKTAMI; Tuti Khairani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Helmi oktami. Nim 0801134140. Implementation By The Department Of Transportation Public Service City Pekanbaru (Parking Management Case Study In Subdistrick Sukajadi).This research was conducted at the Department of Transportation in Pekanbaru is the implementation of a public service by the city transportation department pekanbaru (Parking Management Case Study In Subdistrick Sukajadi) which aim to find out how the implementation of public services by the city transportation department pekanbaru (Study of the parking management in the district Sukajadi).The purpose of this study was to investigate the implementation of public services by the city transportation department pekanbaru (Parking Management Case Study In Sub Sukajadi), and the factors that affect the implementation of public services by the city transportation department pekanbaru (Parking Management Case Study In Subdistrick Sukajadi).The method used in this study is the type of data collected consist of primary data that the data was obtained directly from informants UPTD head parking, parking UPTD staff, and the community that the object of research in the form of information that is relevant to the issues that are being formulated in the study . Include: such as interviews, observations or written remarks. As well as secondary data includes data ie data obtained from the documents and reports that are related to the research problem and also books relating to this research. While the techniques used pengumpalan data is guided interviews, observation and and literature.Techniques of data analysis in this study is done by using data processed using qualitative methods Where the data obtained from interviews onwards systematically described with reference to the theoretical foundation or government regulations that relate to the discussion to find solutions to problems.From these results it can be concluded that the implementation of public services by the city transportation department pekanbaru (Parking Management Case Study In Subdistrick Sukajadi). still not running as expected or can not be considered successful or as expected, it is evident from the respondents or the public. As for the indicators of public services, namely responsiveness, responsibility, accountability, fairness, efficiency, and simplicity.Keywords: Public service, parking management, department of transportation